Relation between insertion torque and tactile, visual, and rescaled gray value measures of bone quality: a cross-sectional clinical study with short implants - Diego Fernandes Triches; Fernando Rizzo Alonso; Luis André Mezzomo; Danilo Renato Schneider; Eduardo Aydos Villarinho; Maria Ivete Rockenbach; Eduardo Rolim Teixeira; Rosemary Sadami Shinkai (SpringerOpen, 2019)
Abstract Background This study assessed the relationship between insertion torque and bone quality evaluated during surgery and in preoperative computed tomographic (CT) images analyzed either visually or by rescaled mean gray values (MGVs). The study also tested the correlation between the clinical and radiographic measures of bone quality. Methods The consecutive sample was composed of 45 short implants (4.1 × 6 mm) placed in the posterior region of 20 patients. Intra-surgical tactile bone quality, based on the classification of bone types by Lekholm and Zarb, and insertion torque were recorded during the implant placement. Visual bone quality and normalized MGV were assessed in standardized axial, coronal, and sagittal sections of preoperative CT images. Data were analyzed by ANOVA and Spearman correlation (alpha = 0.05). Results Insertion torque was associated with all assessment methods of bone quality (tactile, CT visual, MGV). A moderate correlation was found among all methods of bone quality, except for CT visual assessment and tactile evaluation. MGVs varied as a function of arch, dental region, insertion torque, and bone types. Conclusions The results suggest that bone quality measures affect primary stability as recorded by insertion torque, and the assessment methods are consistently related.